Maritime Networks in the Mycenaean World - Tartaron, Thomas F. (EBL-Schweitzer, 2013)
Contents; Figures; Tables; Preface; Acknowledgments; One The Problem of Mycenaean Coastal Worlds; An Archaeological and Historical Problem; Defining Mycenaean Coastal Worlds; Organization of the Book; Two Mycenaeans and the Sea; A Brief Historical Sketch of the Mycenaean Period; Emergence of Mycenaean Civilization; The Palatial Period; Decline and Collapse; Mycenaean Long-Distance Maritime Activity; The Geography and Chronology of Mycenaean Maritime Activity; The Frequency and Volume of Interregional Trade; Direct and Indirect Contact; Mechanisms of Trade